A study on fitting SPHINCS+ to blockchain usage - Lucena, Antônio Unias de; Henriques, Marco Aurélio Amaral (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2020)
The advent of a large-scale quantum computer will make insecure the current leading blockchains' digital signature schemes. Among the quantum-resistant options for signature schemes, SPHINCS+ stands out due to its security (based solely on hash functions) and due to being stateless. However, when used in a blockchain environment, its signature size considerably reduces the number of transactions stored per block, impacting the blockchain operation and economics. This paper presents a study on fitting SPHINCS+ to blockchain usage. The results show that, without compromising the security, a careful choice of SPHINCS+ parameters can reduce both the signature size and the signature creation time, since the maximum number of signatures supported by a given key is limited to 16 million, a number considered more than sufficient for a blockchain environment.